Reactive species in advanced oxidation processes: Formation, identification and reaction mechanism - Wang, Jianlong; Wang, Shizong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Possible reactive species formed in various AOPs were summarized.•Formation mechanisms and influencing factors of reactive species were analyzed.•Various methods for identifying reactive species formed in AOPs were introduced.•Reaction mechanisms of different reactive species with pollutants were discussed. The formation, identification and reaction mechanism of reactive species in various advanced oxidation processes (AOPs) are crucial for understanding the principles of AOPs and the degradation mechanism of recalcitrant organic contaminants because reactive species are responsible for the degradation of organic contaminants in AOPs. In this review, the possible reactive species generated in various AOPs (such as Fenton oxidation, photochemical oxidation, electrochemical oxidation, ozonation, gamma ray/electron beam radiation, persulfate-based oxidation, wet air oxidation and ultrasonic oxidation), were systematically analyzed and summarized, including hydroxyl radicals (HO), hydrogen radical (H), hydrated electron (eaq−), sulfate radicals (SO4−), peroxymonosulfate radicals (SO5−), superoxide radicals (O2−), singlet oxygen (1O2) and hydroperoxy radicals (HO2). The factors that influence the formation of reactive species were discussed, mainly including pH, inorganic anions and dissolved organic matter. The main identification methods, such as electron spin resonance (ESR), electron paramagnetic electron (EPR), high performance liquid chromatography (HPLC), transient absorption spectrum, quenching experiments and kinetic analysis, were introduced, and the reaction mechanism of reactive species with organic contaminants were discussed. Finally, concluding remarks and perspectives were proposed. This review paper will provide an insight into the formation, identification and reaction mechanism of reactive species in AOPs, which is helpful for reader to better understand the degradation mechanism of recalcitrant organic contaminants in various AOPs.